Implementasi Administrasi Operasional di CV. Stara Maju Perkasa - Anti Wulan Agustini; Intan Maharani (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
Community service is a form of implementation of the Tri Dharma of Higher Education which aims to make a real contribution to society through the application of knowledge and skills possessed by students. The rapid development of the business world requires every company to be able to manage operational activities effectively and efficiently. In carrying out company activities, administration has an important role in regulating various activities related to data recording, document management, and archiving company information. This service activity was carried out at CV. Stara Maju Perkasa with the aim of assisting in the implementation of more orderly and systematic operational administration. The method used is a descriptive method with a participatory approach through observation, interviews, and assistance in operational administration activities. The results of the activity show that the implementation of operational administration can improve the neatness of data recording, document management, and archiving of company archives so as to facilitate the process of searching for information. In addition, this activity also improves employee work efficiency and minimizes errors in administrative management. Thus, the implementation of good operational administration is able to support the smooth running of the company's activities as a whole.